MANAJEMEN PROGRAM HALAQOH AL QURAN DI MADRASAH TSANAWIYAH AN NUR BULULAWANG MALANG - Rahmat Hidayatullah; Illyas Thohari; Devi Wahyu Ertanti (VICRATINA, 2020)
In this era, the increasing population of the population has an impact on the number of religious associations such as the community tahlil village, reading the prophet's birthday, and majlis ta'lim. However, with the increase in the association is not balanced by the increasing number of adolescents who are able to become the next generation in the association, which is only dominated by elderly people who may not be able to survive until the next generation. The purpose of this study is to describe the Al-Qur'an curricular learning planning for the halaqoh approach, the implementation and assessment of the halaqoh program in improving the ability to read the Qur'an. Which later someone who can read the Qur'an can be useful in society. This research uses descriptive qualitative research with case study research type, where this type of strategy is open and flexible with a deep focus to systematically compile descriptions. The location chosen by the researcher was Madrasah Tsanawiyah An-Nur Bululawang. The subjects of the study were students of Madrasah Tsanawiyah An-Nur Bululawang as well as the process of halaqoh activities and informants from the chief executive and Ustadz halaqoh.